Management of extensive subcutaneous emphysema using negative pressure wound therapy dressings - Huan, Nai‐Chien (Respirol Case Rep, 2020)
Subcutaneous emphysema (SE) is a common but usually self‐limiting complication of cardiothoracic procedures. Rarely, it can be life threatening and is characterized by extensive cutaneous tension and airway compromise requiring immediate intervention. There is a paucity of data on the most efficacious treatment methods for extensive SE. We report an 80‐year‐old gentleman who developed massive SE necessitating intubation for airway protection following a right chest tube insertion for spontaneous secondary pneumothorax. His SE persisted despite adequate thoracic drainage via a new chest tube. It was then decided to insert two negative pressure wound therapy dressings (NPWTD) or vacuum dressings in the patient's subcutaneous tissue layer via incisions made at anterior chest wall. The dressings were removed after four days in view of significant improvements. NPWTD appears to be an effective, well‐tolerated, safe, and inexpensive approach that hastens the resolution of SE without the need for invasive thoracic surgeries.